Probing fMRI brain connectivity and activity changes during emotion regulation by EEG neurofeedback - Dehghani, Amin; Soltanian-Zadeh, Hamid; Hossein-Zadeh, Gholam-Ali (Frontiers in Human Neuroscience, 2023)
Despite the existence of several emotion regulation studies using neurofeedback, further investigation is needed to understand the interactions of the brain regions involved in the process. We implemented EEG neurofeedback with simultaneous fMRI using a modified happiness-inducing task through autobiographical memories to upregulate positive emotion. The participants in the control and experimental groups were asked to do emotion regulation while viewing positive images of autobiographical memories and getting sham or real (based on alpha asymmetry) EEG neurofeedback, respectively. The proposed multimodal approach quantified the effects of EEG neurofeedback in changing EEG alpha power, fMRI BOLD activity of prefrontal, occipital, parietal, and limbic regions (up to 1.9% increase), and functional connectivity in/between prefrontal, parietal, limbic system, and insula in the experimental group. New connectivity links were identified by comparing the brain functional connectivity between experimental conditions (Upregulation and View blocks) and also by comparing the brain connectivity of the experimental and control groups. Psychometric assessments confirmed significant changes in positive and negative mood states by neurofeedback in the experimental group. For the brain regions involved in emotion regulation, we found significant BOLD and functional connectivity increases due to neurofeedback in the experimental group but no learning effect was observed in the control group. The results reveal the neurobiological substrate of emotion regulation by the EEG neurofeedback and separate the effect of the neurofeedback and the recall of the autobiographical memories.